Canada's approach to quantum in security and economics: feminist foreign policy or tokenizing #WomenInSTEM? - Murphy, Michael P.A. (Canadian foreign policy journal, 2024)
The Canadian government has released major strategy documents relating to quantum science, technology, and security in recent years. While these emerge within a broader context of self-styled "feminist" policymaking, this article represents the first study to assess the quantum strategy frameworks along the lines of feminist policymaking. After providing context to the quantum landscape in Canada, the article undertakes a close reading of the National Quantum Strategy and the DND/CAF Quantum S&T Strategy to highlight the neglect of substantive feminist considerations in formulating these policies. While the documents highlight the disruption that the development of quantum technologies will bring to society, the strategies ignore the potential for differential impacts of this disruption. This neglect of the gendered impacts of quantum disruption is especially damning for the Canadian quantum strategy given the substantial reliance on Canada's reputation and branding as an ethical actor in world politics. The article concludes with a discussion of future research that is necessary to remediate this strategic failure.